2000
DOI: 10.1258/0022215001905643
|View full text |Cite
|
Sign up to set email alerts
|

Unusual presentations of isolated sphenoid fungal sinusitis

Abstract: Isolated sphenoid fungal sinusitis is a rare and often difficult to diagnose condition as the presenting symptoms are often vague and non-specific. In this series each case has a different clinical presentation with a different causative fungus. Although isolated fungal sphenoid sinusitis is usually seen in immunocompromised individuals, two of the three cases presented were immunocompetent. The fungi were Pseudallescheria boydii, Aspergillus fumigatus and Schizophyllum commune. In order to illustrate the grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Predominant clinical findings are slight swelling of the face over the infected sinus, followed by nasal hypesthesia, pallor, and bleeding. The disorder is more common in arid climates [211]. Presence of fungus balls may lead to bone erosion due to pressure necrosis [212].…”
Section: Characteristics Of Diseasementioning
confidence: 99%
“…Predominant clinical findings are slight swelling of the face over the infected sinus, followed by nasal hypesthesia, pallor, and bleeding. The disorder is more common in arid climates [211]. Presence of fungus balls may lead to bone erosion due to pressure necrosis [212].…”
Section: Characteristics Of Diseasementioning
confidence: 99%
“…Its surgical treatment alone is not adequate, and it must be combined with antifungal treatment (7). Furthermore, adjunctive antifungal therapy has been suggested to guard against the risk of dissemination or recurrence of the disease (8)(9)(10)(11). Despite the increasing clinical importance of S. commune, information on its molecular identification and antifungal susceptibility profile is scanty and limited to a small number or individual isolates (4,12).…”
mentioning
confidence: 99%
“…Among the 29 globally reported cases of S. commune infection who had received antifungal therapy, there were 11 cases each with ABPM, 9 with sinusitis, 4 with bronchial mucoid impaction, and 1 case each with brain abscess, ulcer of the palate, fungal ball, bronchopneumonia, and pulmonary nodule (4,(7)(8)(9)(10). Of the 18 patients treated with itraconazole, all of them responded favorably without recurrence (4, 8-10, 19, 20, 24-31, 33-35).…”
mentioning
confidence: 99%
“…Parker et al [26] and Shaw et al [31] in their report suggested the significant correlation between isolated fungal sinusitis and immunocompromised patients. Dubey et al [10] reported that diabetes mellitus (DM) was the most immunocompromising factor and present in 40 % of reported patients with CNS fungal infections.…”
Section: Discussionmentioning
confidence: 94%